Adjuvant chemotherapy in elderly patients with breast cancer: key challenges. Issue 6 (2nd June 2016) - Pondé, Noam; Dal Lago, Lissandra; Azim, Hatem A.
ABSTRACT: Elderly women with early breast cancer (BC) form a heterogeneous and large subgroup (41.8% of women with BC are over 65). Decision making in this subgroup is made more difficult by lack of familiarity with their physical, cognitive and social issues. Adequate management depends on biological factors and accurate clinical evaluation through comprehensive geriatric assessment (CGA). CGA can help to better select and determine potential risks factors for patients who are candidates for adjuvant chemotherapy. It is still recently introduced in geriatric oncology and there is a lack of awareness of its importance. Available data on adjuvant chemotherapy for BC is limited but suggests it can be of benefit for well selected patients, though the risk of short and long-term toxicity is significant. Here we provide a discussion of the key practical issues in decision making in the setting of adjuvant chemotherapy for elderly BC patients.